Whole Language and Phonics: Which Instructional Practices are Most Effective in Teaching At-Risk Students to Read? (Kairaranga, 2015)
A disproportionate number of New Zealand students fail to learn to read. Children from low socio-economic backgrounds are over-represented among New Zealand’s under-achieving readers. This study investigated the extent to which teachers of beginning readers in low-decile schools emphasised explicit phonological-based instruction, as well as the relationship between teacher emphasis on phonological instruction and student progress in reading-related skills. Results demonstrated that children from different literacy instruction programmes progressed similarly in all reading-related skills except word reading. Students receiving explicit phonological- based literacy instruction made superior progress in word reading skills over children receiving implicit phonological-based instruction. A strong emphasis on explicit phonological instruction was also associated with a reduction in variation of class word reading scores over time. The study findings support previous research demonstrating that phonological awareness and decoding skills play a crucial role in the development of word reading ability and that explicit phonological-based instruction can attenuate differences in word reading development. Implications for teachers and policy makers are described.